Spatio-temporal variations in carbon sources, sinks and footprints of cropland ecosystems in the Middle and Lower Yangtze River Plain of China, 2013–2022 - Jing Kong; Yisong Li (Scientific Reports)
Abstract Cropland ecosystems, which are most affected by human activities, are dual carriers of carbon sources and sinks. It has significant implications for the achievement of the “two-carbon” objective. The Middle and Lower Yangtze River Plain (MLYRP) is the principal grain-producing area of China, which is a great agricultural country. The development of green agriculture in this plain is of vital importance. Nevertheless, there is a lack of attention to the dynamics of the carbon footprints of cropland. Hence, this study was conducted with the help of carbon emission coefficient method. It investigated the spatio-temporal variations of carbon sources, sinks and carbon footprints of cropland ecosystems in this plain from 2013 to 2022. The findings suggest that (1) Carbon uptake was fluctuating up during the study period. Carbon uptake was higher in paddy and wheat. (2) Carbon emissions were declining year by year. Fertilizer and irrigated agriculture produced more carbon emissions. The top four for both indicators were Anhui, Jiangsu, Hubei and Hunan provinces. (3) The carbon footprint declined in fluctuations. This indicator ranked the top four in Hubei, Anhui, Zhejiang and Jiangsu provinces. The spatial distribution pattern of the above three indicators was more in the north and less in the south. (4) Cropland ecosystems exhibited carbon sinks. There were relatively large carbon eco-surplus and high carbon eco-efficiency. Nevertheless, the carbon ecological surplus was decreasing in fluctuation. Consequently, MLYRP should keep popularizing new technologies such as green manure crops and precision agriculture.